European Union Entrepreneurship and Innovativeness Support Policy for Businesses; Polityka Unii Europejskiej wspierania przedsiebiorczosći i innowacyjnosćina rzecz przedsiebiorstw - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2012)
The development of entrepreneurship as well as research and innovation have direct impact on growth in the level of economic development as well as the prosperity of individual citizens and society in general. The primary goal of policies involving research and technological development is establishing the European Union as a leading knowledge-based economy. Innovativeness is also the main factor in improving the competitiveness of companies. The key to improving the economic situation in Poland is the strengthening of innovative attitudes among entrepreneurs. An efficiently running institutional system guaranteeing effective support instruments for entrepreneurs and the scientific-research sphere as well as guaranteeing the unhindered transfer of knowledge should prove helpful. As the main factor in improving the competitiveness of companies, innovativeness is mainly the result of the development of collaboration between the spheres of science and business as well as the use of patent achievements in companies. The drive behind future growth in the European Union will be sectors based on knowledge and innovation. However, these require a solid industrial network and resources allowing the utilization of new technologies. To a great extent, growth in entrepreneurship and innovativeness as significant factors in the economic development of Europe and Poland is dependent on the elimination of administrative barriers for companies and the introduction of the facilitating of information and communication (ICT) as needed for them to function. – – Rozwoj́ przedsiebiorczosći oraz badania i innowacje bezposŕednio przyczyniaja sie do wzrostu poziomu rozwoju gospodarczego oraz dobrobytu poszczegoĺnych obywateli i ogoĺu społeczenśtwa. Głoẃnym celem polityki w zakresie badaní rozwoju technologicznego jest ustanowienie Unii Europejskiej jako wiodacej gospodarki opartej na wiedzy. Innowacyjnosćj́est tezġłoẃnym czynnikiem poprawy konkurencyjnosći przedsiebiorstw. Kluczowe dla poprawy sytuacji gospodarczej w Polsce jest wzmocnienie postaw innowacyjnych wsŕod́ przedsiebiorcoẃ. Pomoć mozė w tym sprawnie działajacy system instytucjonalny, ktoŕy zapewni efektywne instrumenty wsparcia dla przedsiebiorcoẃ i sfery naukowo-badawczej oraz zagwarantuje swobodny transfer wiedzy. Innowacyjnosćj́ako głoẃny czynnik poprawy konkurencyjnosći przedsiebiorstw wynika głoẃnie z rozwoju wspoĺpracy miedzy sfera nauki i biznesu oraz z wykorzystywania osiagniecṕatentowych w firmach. Motorem przyszłego wzrostu w UE beda sektory oparte na wiedzy i innowacjach, wymagajace jednak solidnej sieci przemysłowej i sŕodkoẃ pozwalajacych na wykorzystanie nowych technologii. Wzrost przedsiebiorczosći i innowacyjnosći jako istotnych czynnikoẃ rozwoju gospodarczego w Europie i w Polsce zalezȧ w duzẏm stopniu od znoszenia barier administracyjnych dla przedsiebiorstw i wprowadzania ułatwienínformacyjnych i komunikacyjnych (ICT) dla ich funkcjonowania.
Keywords: 330